The Role of Acupuncture in Hormonal Shock-Induced Cognitive-Related Symptoms in Perimenopausal Depression: A Randomized Clinical Controlled Trial - Zhou, Jun-He; Zhang, De-Long; Ning, Bai-Le; Xue, Xiao-Juan; Zhao, Lin; Wu, Qian; Yan, Lu-Da; Liu, Ming; Fu, Wen-Bin (Frontiers in Psychiatry, 2022)
Abstract Introduction Perimenopausal depression is predominantly caused by hormone shock, but the underlying physical and psychological factors are still unclear. Objectives To explore the constituent components of perimenopausal depression by dynamically depicting its influencing factors and interactive pathways from the perspective of embodied cognition. Methods This is a randomized clinical controlled trial. In this study, electroacupuncture was compared with escitalopram. A total of 242 participants with mild to moderate perimenopausal depression were enrolled from 6 hospitals in China. Each participant had a 12-week intervention and a 12-week follow-up period. The primary outcome of this study is the Hamilton Depression Rating Scale (HAMD-17), and the secondary outcome is the menopause-specifc quality of life scale (MENQOL), serum Follicle-stimulating hormone (FSH), luteinizing hormone (LH), and estrogen (E2) levels. Results The structural equation model suggested that hormone levels were not directly associated with HAMD-17 (P=0.852), while MENQOL was statistically correlated with HAMD-17 as an intermediary variable (P＜0.001). Electroacupuncture gradually showed positive impacts on MENQOL and HAMD-17 during the follow-up period (P＜0.05). Cognitive impairment is the dominant dimension of perimenopausal depression. Conclusions. Hormonal shock may affect clinical symptoms and poor quality of life to induce cognitive impairment leading perimenopausal depression, and this impact on cognition is embodied. Electroacupuncture has positive effect on perimenopausal depression and quality of life.